Prospective scientific and technological analysis about cancer related to the head and neck region (Research, Society and Development, 2023)
They are also known as head and neck squamous cell carcinoma and are a biologically diverse and genetically heterogeneous disease. Due to the advanced condition, surgical resection of the tumor and lymph node drainage are widely used, especially with subsequent radiation associated or not with chemotherapy. Because the treatment is based primarily on surgery, followed by radio or chemotherapy, the patient's quality of life is impacted and ends up influencing the improvement of the condition in general. The present study aimed to carry out a mapping of Technological and Scientific Prospecting in a systematic qualitative and quantitative way in search of scientific articles and patents regarding cancers related to the head and neck region and their developed immunotherapies. Science Direct and PubMed were used as databases for scientific prospecting and, for technological prospecting, the Google Patents database was used. Publications were limited between the years 2012-2022 and documents made available in full were selected, in order to cover as many articles as possible directed to the objective of the study based on a refinement using the descriptors “head and neck cancer; immunotherapies; therapeutic vaccines”. It can be seen that immunotherapy is a path to this type of sought-after alternative. It was possible to observe that there is a need for studies in this area due to its importance for people's quality of life.